Beliefs and Practices in the Life Cycle of the Agtas of Lupigue, Ilagan, Isabela, Philippines: Its Implications to Social Development - Abon, Edizon B; Garcia, Judith R; Reyes, Agnes S (SUSURGALUR, 2016)
ABSTRACT: The Philippines is a nation blessed with several ethnic groups. This condition makes the Filipinos socially and culturally different. The Filipino character is actually a combination of the Eastern and Western cultures. The study attempted to find out the beliefs and practices in the life cycle of the Agta of Lupigue, Ilagan, Isabela, Philippines and their social implications. The ethnographic research method was used to attain the purposes of this study. Structured and unstructured interview and participant observation were conducted to confirm and validate the data gathered through field study. Documentary analysis was employed to draw vital information on the origin of the Agta and the community where they live. Findings of the study revealed that among the Agta of Lupigue, there are beliefs that are consistently practiced and observed. This study poses a great challenge to social scientist, especially in their role as agent of social transformation. The study recommends that social scientists and educators should commit to the religious implementation of the regeneration of the IPs (Indigenous Peoples) beliefs and practices that are considered beneficial and practical. KEY WORDS: Beliefs and Practices; Life Cycle; Agtas of Lupigue; Social Scientists and Educators; Social Implications.Â IKHTISAR: âKeyakinan dan Praktek dalam Siklus Kehidupan Suku Agtas dari Lupigue, Ilagan, Isabela, Filipina: Implikasinya untuk Pembangunan Sosialâ. Filipina adalah negara yang diberkati dengan beberapa kelompok etnis. Kondisi ini membuat bangsa Filipina secara sosial dan budaya berbeda. Karakter bangsa Filipina sebenarnya merupakan kombinasi antara budaya Timur dan Barat. Penelitian ini berusaha mengetahui keyakinan dan praktek dalam siklus kehidupan suku Agta dari Lupigue, Ilagan, Isabela, Filipina dan implikasi sosialnya. Metode penelitian etnografi digunakan untuk mencapai tujuan penelitian. Wawancara terstruktur dan tidak terstruktur serta observasi partisipatif dilakukan untuk mengkonfirmasi dan memvalidasi data yang dikumpulkan melalui studi lapangan. Analisis dokumenter dikerjakan untuk menarik informasi penting tentang asal-usul suku Agta dan masyarakatnya di mana mereka tinggal. Temuan penelitian menunjukan bahwa diantara suku Agta dari Lupigue, ada keyakinan yang konsisten dipraktekkan dan dihayati. Penelitian ini merupakan tantangan besar untuk ilmuwan sosial, terutama dalam peran mereka sebagai agen transformasi sosial. Penelitian merekomendasikan bahwa ilmuwan sosial dan pendidik harus berkomitmen dalam pelaksanaan keagamaan suku asli secara regenerasi tentang keyakinan dan praktek yang dianggap menguntungkan dan bersifat praktis.KATA KUNCI: Keyakinan dan Praktek; Siklus Kehidupan; Suku Agtas dari Lupigue; Ilmuwan Sosial dan Pendidik; Implikasi Sosial.Â Â About the Authors: Prof. Edizon B. Abon, Prof. Judith R. Garcia, and Prof. Dr. Agnes S. Reyes are the Lecturers at the PNU (Philippine Normal University), North Luzon, Alicia, Isabela, Philippines. For academic interests, the authors can be contacted via e-mail at: garcia.jr@pnu.edu.phHow to cite this article? Abon, Edizon B., Judith R. Garcia & Agnes S. Reyes. (2016). âBeliefs and Practices in the Life Cycle of the Agtas of Lupigue, Ilagan, Isabela, Philippines: Its Implications to Social Developmentâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.4(1) March, pp.51-64. Bandung, Indonesia: Minda Masagi Press and UBD in Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808. Chronicle of the article: Accepted (November 25, 2015); Revised (January 25, 2016); and Published (March 30, 2016).